Does chlorhexidine reduce bacteremia following tooth extraction? A systematic review and meta-analysis. - Iciar Arteagoitia; Carlos Rodriguez Andrés; Eva Ramos (PLoS ONE, 2018)
Background and aims Scientific evidence is not clear regarding the use of antimicrobial mouth rinse before dental extraction to reduce bacteremia. We tested the null hypothesis that there would be no difference in the incidence of bacteremia following dental extractions in patients treated with or without chlorhexidine. Material and methods We conducted a meta-analysis following the recommendations proposed by PRISMA Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The data sources Pubmed, Cochrane, Web of Science, Science Direct, Scopus, and Ovid MD were searched until April 30, 2017. (chlorhexidine) AND (bacteremia OR bacteraemia) AND (extraction OR removal) were used as key words in a free-text search. Published meeting abstracts were searched. The references of each article were reviewed. We only included randomized controlled clinical trials. There were no restrictions regarding language or date of publication. The outcome measure was the incidence of the bacteremia measured within the first ten minutes post-extraction. Two reviewers independently undertook the risk of bias assessment and data extraction. A fixed-effects inverse variance weighted meta-analysis was conducted. Results Out of 18 studies, eight eligible trials with 523 participants were selected, 267 in the experimental group and 256 in the control group: risk ratio = 0.882 (95% confidence interval 0.799 to 0.975; p = 0.014), heterogeneity I2 = 13.07%, and p = 0.33. The number needed to treat was 16 (95% CI 7-Infinity). Conclusions Approximately 12% of bacteremia cases can be prevented if a population is exposed to chlorhexidine. CRD42016046586.